KAJIAN PERSIMPANGAN BERSINYAL JALAN BASUKI RAHMAT – JALAN AGUS SALIM – JALAN ABUL HASAN DI KOTA SAMARINDA - YANSYAH, ARDI (KURVA S JURNAL MAHASISWA, 2014)
Ardiyansyah, NPM: 10.11.1001.7311.186, signalized Intersection Study Basuki Rahmat road- Agus Salim road Abul Hasan in the city of Samarinda, Supervisor I: Ir. Yayuk Sri Sundari, MT,and       Advisor            II:Rosa     Agustaniah,ST,MT.             Samarinda is the capital city of East Kalimantan has a very strategic location connecting several districts / cities in this area, so that the growth of the city of Samarinda pretty high every year. This situation causes an imbalance between the number of vehicles on the road with the available capacity, resulting traffic problems and traffic accidents as well as long queues of vehicles.             As happened at the Crossroads-Jalan Basuki Rahmat Agus Salim- Abul Hasan Road intersection around this area is the Department offices and shops. Many of the vehicles that enter the intersection area, so during peak hours (peak hours) frequent delays. For that there must be a re-evaluation of the performance of the intersection. The purpose of this study is to analyze the performance of traffic lights at the junction of Jalan Basuki Rahmat-road Sehwan Agus Salim - Road Abul Hasan by means of the method Indonesian Highway Capacity Manual 1997 (MKJI'97). The purpose of this study is as follows:             1. Analyze the initial conditions at peak hours and the average of the performance of signalized intersections as well as the service level (the level of service / LOS)             2. Analyzing the conditions change during the peak hours of traffic lights and the average of the performance of signalized intersections as well as the service level (the level of service / LOS) From the analysis of signalized intersection at Basuki Rahmat road Agus Salim-Road Abul Hasan is concluded; 1 Based on the analysis of the performance of the intersection of the initial conditions             a. Obtained at peak hours of service Level (level of service / LOS) initial conditions averaged intersection v / c = 1.42> 0.85 have a level of service (LOS) = F, or forced flow of traffic, low speed, volume below capacity, many vehicle stops.             b. Obtained an average hourly rate of services (level of service / LOS) initial conditions averaged intersection v / c = 1.05> 0.85 have a level of service (LOS) = F, or forced flow of traffic, low speed, volumes below capacity, many vehicle stops. 1 Based on the analysis of changes in conditions at the time the traffic light intersection;             a. Obtained at peak hours of service Level (level of service / LOS) initial conditions   averaged intersection v / c = 0.731 <0.85 have this level of service (LOS) = C, steady flow, the speed is controlled by the flow of traffic, the driver is limited in choosing speed.             b. Obtained an average hourly rate of services (level of service / LOS) initial conditions averaged intersection v / c = 0.542> 0.85 have a level of service (LOS) = C, steady flow, the speed is controlled by the flow of traffic, the driver constrained in choosing speed.